The burden of endometriosis in China from 1990 to 2019 - Wang, Yan; Wang, Xiaoyan; Liao, Kaijun; Luo, Baoqin; Luo, Jiashou (Frontiers in Endocrinology, 2022)
Background The trends in deaths from and disability-adjusted life years (DALY) of endometriosis in China remain largely unknown. This study revealed these trends and the effects of age, period, and cohort on the death from and DALY of endometriosis in China from 1990 to 2019. Methods Data on endometriosis death and DALY in China between 1990 and 2019 were obtained from the Global Burden of Disease Study 2019 (GBD 2019). The annual percentage change and average annual percent change (AAPC) were analyzed by joinpoint regression. The effects of age, period, and birth cohort on death and DALYs were estimated using an age–period–cohort analysis. Results The age-standardized death rate (ASDR) and age-standardized DALY rate for endometriosis significantly decreased in China, with AAPC values of −4.7 (95% confidence interval [CI]: −5.10, −4.30) and −1.2 (95% CI: −1.20, −1.10), respectively. The joinpoint regression analysis showed that the ASDR and age-standardized DALY rate decreased across all age groups. Moreover, the effect of age on endometriosis death and DALY decreased with advancing age. Both the period and cohort effects on endometriosis death and DALY showed decreasing trends, with the effects on death decreasing faster than the effects on DALY. Conclusions The endometriosis ASDR and age-standardized DALY rate decreased from 1990 to 2019. The effects of the period and birth cohort on endometriosis death and DALY showed a declining trend across all age groups. The effect of age on endometriosis deaths and DALYs decreased with advancing age.